BIM as a Pedagogical Tool for Teaching HVAC Systems to Architecture Students - Mokhtar, Ahmed (2019)
Understanding the basics of Environmental Control Systems including HVAC systems is required in architectural curricula. One of the challenges of learning this subject is the nonfamiliarity of the students with the components of these systems and how the selection and installation of these components can impact the architecture of the building and its spacial experience. Such difficult interrelationships can be clarified using various techniques. One technique that the author experimented with is the use of a BIM tool. Yet, using the tool to achieve this purpose had been a challenge in itself. The tool needs to be setup and its interface needs to be configured for a particular learning objective within a defined learning environment. This paper discusses the various techniques to achieving the learning of this required subject. It also shares the details of preparing and executing the experiment of using BIM hoping that other instructors make use of it and further build on it. A survey of the students who went through the experiment shows that a large majority believes that they learned the subject better through the BIM tool.